Cardioprotective mechanisms of sodium-glucose cotransporter 2 inhibitors - A. M. Mkrtumyan; T. N. Markova; N. K. Mishchenko (Сахарный диабет)
The findings of large-scale cardiovascular outcome trials have been demonstrated that sodium-glucose cotransporter 2 inhibitors (iSGLT-2) have shown beneficial cardiovascular effects. In this review proposed mechanisms underlying iSGLT-2-associated cardiovascular benefits have been discussed: haemodynamic and intracellular effects, including metabolic effects and electrolyte changes; and also, the effect on markers of cardiovascular disease (CVD). The hemodynamic effects of SGLT-2 are characterized by reduction of cardiac preload and afterload as a result of osmotic diuresis, a decrease in blood pressure and arterial stiffness. The metabolic effects of this medicine are accompanied by an increase the production of ketone bodies, followed by improving ATP production and myocardial energetics. Also, iSGLT-2 modulate ion transporters (NHE1 and NHE3). A reduction of cytoplasmic sodium and calcium levels and increasing mitochondrial calcium levels in the cardiomyocytes enhances the synthesis of ATP and increases cell viability. Effect of iSGLT-2 on CVD markers showed a decrease in the levels of the N-terminal pro-B-type natriuretic peptide and highly sensitive troponin I in elderly patients with type 2 diabetes mellitus (T2DM). Thus, this class of agents has a multifactorial effect on the functioning of cardiovascular system. Further studies will help to explain the all possible cardioprotective effects of iSGLT-2 in individuals with and without T2DM.